2007
DOI: 10.1103/physreve.76.036406
|View full text |Cite
|
Sign up to set email alerts
|

Wave packet simulation of dense hydrogen

Abstract: Dense hydrogen is studied in the framework of wave packet molecular dynamics. In this semiquantal many-body simulation method the electrons are represented by wave packets which are suitably parametrized. The equilibrium properties and time evolution of the system are obtained with the help of a variational principle. At room temperature the results for the isotherms are in good agreement with anvil experiments. At higher densities beyond the range of the experimental data a transition from a molecular to a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…4 Ω -1 cm -1 , as calculated in [7,11,30]. We found that the drop in resistance at the point of hydrogen melting was less pronounced Fig.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…4 Ω -1 cm -1 , as calculated in [7,11,30]. We found that the drop in resistance at the point of hydrogen melting was less pronounced Fig.…”
Section: Resultssupporting
confidence: 49%
“…A metallic-like state might appear due to narrowing of the band gap with increasing temperature [7,9,11]. Currently available experimental data are insufficient to enable us to discriminate among the above scenarios.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its seemingly simple composition, hydrogen is known to have a variety of complex phases [1]. Moreover, both experimental [2][3][4][5][6][7][8][9] and theoretical [10][11][12][13][14][15][16] methods have so far failed to give conclusive answers concerning the existence of a plasma phase transition, the nature of the molecular to atomic transition in the high density fluid, the location of the metallization transition in the solid, the melting line for pressures higher than 250 GPa [17] and the question of a possible liquid at T = 0 K connected to it [18].…”
mentioning
confidence: 99%